Cytokine profiles and antibody responses to Plasmodium falciparum malaria infection in individuals living in Ibadan, southwest Nigeria (2009)
Background: The ability of the host immune system to efficiently clear Plasmodium falciparum parasites during a malaria infection depends on the type of immune response mounted by the host. Study design: In a cross-sectional study, we investigated the cellular-and antibody responses in individuals with P. falciparum infection, in an attempt to identify immunological signs indicative of the development of natural immunity against malaria in Ibadan, Nigeria. Levels of IL-10, IL-12(p70), IFN-γ, and IgM, IgG and IgG1-4 subclasses in the serum of 36 symptomatic children with microscopically confirmed malaria parasitaemia and 54 asymptomatic controls were analysed by ELISA. Results: IFN-γ and IL-10 were significantly higher in the symptomatic children (p=0.009, p=0.025 respectively) than in the asymptomatic controls but no differences were seen for IL-12(p70). Estimated higher ratios of IFN-γ/IL-10 and IFN-γ/IL-12 were also observed in the symptomatic children while the asymptomatic controls had higher IL-12/IL-10 ratio. The mean concentration levels of anti-P. falciparum IgG1, IgG2, IgG3 antibodies were statistically significantly higher in the individuals >5 years of age than <5 years while anti-P. falciparum IgG3 antibodies were notably low in <5 years category. Children <5 years had higher IgM antibodies than IgG and the expression of IgG subclasses increased with age. Conclusion: Taken together, malaria infection is on a delicate balance of pro- and anti-inflammatory cytokines. The higher levels of IFN-γ seen in the symptomatic children (<6months) may be instrumental in immune-protection against malaria by limiting parasite replication. The observed variations in immunoglobulin subclass levels were age-dependent and exposure-related